Global Space Security and Counter-space Capabilities: the Legal and Political Challenges - Polkowska, Małgorzata (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
This article undertakes a very sensitive issue: space security and counterspace capabilities and arms control. Those issues come under the sovereignty of each state and are strictly connected to national defense and policy. Counterspace, also known as space control, is the set of capabilities or techniques that are used to gain space superiority. Space superi-ority is the ability to use space for one`s own purposes while denying it to an adversary. These issues are so important now in the era of fast-growing state activities in space and under such a big dependence on space. Anti-satellite weapons (ASAT) are a subset of offensive counterspace capabilities, although the satellite itself is only one part of the system that can be attacked. That is the reason why protecting space infrastructure, in the absence of stabilized international space control cooperation and difficulties in reaching an agreement on PPWT treaty and lack of progress of international space law in this matter, is crucial by building the Space Situational Awareness system. Collaboration of states in this matter seems to be a priority.